Chemical and Biological Characteristics of Anacardic acid as a Bioactive Compound and Its Application on Ruminant - Elizabeth Wina; Andi Saenab (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
The use of bioactive compounds from plants is becoming a major interest to be used as feed additives to reduce the effect of greenhouse gases on climate changes and as an alternative to antibiotic growth promoter. One of the compounds that have not been widely known and used is anacardic acid. In Indonesia, anacardic acid and its derivates are commonly found in the waste from the cashew nut industry, namely cashew nut shells. The purpose of this paper is to describe the chemical and biological characteristics of anacardic acid and its effects on rumen fermentation and ruminant production. Anacardic acid or cashew nut shell extract that contains anacardic acid have the ability to suppress methane produced in the rumen. In addition, this compound increases propionic acid in the rumen which is useful for ruminant. Up till now, the applications of anacardic acid for ruminants that described in published papers were mostly done in vitro, while its direct application to livestock has not been widely reported and most of its use is combined with other compounds. The utilization of anacardic acid in Indonesia as a feed additive for ruminants will contribute to reducing greenhouse gases and increasing the productivity of ruminants.